Faktor Yang Mempengaruhi Underpricing Pada Perusahaan Yang Melakukan Initial Public Offering (IPO) - Anisa Lukmarda, Merry Susanti (Jurnal Paradigma Akuntansi, 2019)
The purpose of this study is to obtain empirical evidence on the effect of firm internationalization, board size, firm internationalization moderated by CEO ownership, firm internationalization moderated by blockholder ownership on underpricing of companies that made Initial Public Offering (IPO) during 2008-2017, with a total of 43 samples. This study uses secondary data which were tested using moderated regression analysis with EViews. The result of this study suggests that firm internationalization and board size have no effect on underpricing. Results also report that CEO ownership and blockholder ownership have no effect in moderating the interaction between firm internationalization and underpricing